Model of Contemporary Thai Flower Arrangements for Application in Flower Business - Sorose, Apirat; Kaewsrithong, Jiraphat (Arts of Management Journal, 2023)
This article aimed to 1) study contemporary Thai flower arrangements and 2) create a contemporary Thai flower arrangement model for application in the flower business. The study applied mixed methods research conducting document investigations and in-depth interviews. The semi-structured interview was used as a research tool to collect data from three experts. As for the contemporary Thai flower arranging styles for application in the flower business, a group discussion method was conducted among 1) three experts, 2) five committees from Thai National Professional Qualification and Occupational Standards and the Department of Skill Development, 3) five academic educators, and 4) five entrepreneurs. According to the first objective, it was found that there was a rapid change in the social, economic, political, and technological dimensions of the contemporary Thai flower. There was an adaptation of styles, inventions, types of flowers, and methods to keep up with the changing trends with the combination of art and contemporary culture to meet human needs in terms of utility and beauty. In the case of the second objective, the study revealed that the contemporary Thai flower arrangement model for application in the flower business, known as the 4C-FLORIST Model, comprised 11 elements including 1) Customer Segment, 2) Conceptual Design, 3) Convenience to Buy, 4) Consequences, 5) Flower Arranging, 6) Learning, 7) Opportunity, 8) Reform, 9) Identity, 10) Standardization, and 11) Timeliness.